The Diagnostic Challenge of Distinguishing Temporal Lobe Encephaloceles from Sphenoid Sinus Mucoceles - Ein Wan Chin; Liang Chye Goh; Aun Wee Chong (Talenta Publisher, 2024)
Background: Temporal lobe encephaloceles are rare defects involving brain herniation through the skull base, often misdiagnosed as sphenoid sinus mucoceles cystic lesions due to mucus buildup. Both conditions share overlapping neurological, nasal, and ophthalmologic symptoms, but require different treatments. Objective: To emphasize the importance of accurate diagnosis in distinguishing temporal lobe encephaloceles from sphenoid sinus mucoceles and to highlight the role of imaging in clinical management. Methods: A 27-year-old healthy man presented with seizure and loss of consciousness, with a history of head trauma 13 years earlier. Physical examinations, including cranial nerve and cerebellar assessments, were normal. Rigid nasoendoscopy was unremarkable. Imaging included CT and brain MRI. Results: CT scan suggested an expanded left sphenoid sinus likely mucocele with temporal lobe encephalomalacia. Brain MRI confirmed a left temporal lobe encephalocele. The patient underwent successful transcranial repair. Conclusion: Misinterpretation of imaging may lead to incorrect management. Comprehensive evaluation, particularly with MRI, is essential to differentiate encephaloceles from mucoceles for appropriate treatment planning.